Access to Nature via Virtual Reality: A Mini-Review - Li, Hansen; Zhang, Xing; Wang, Hongying; Yang, Zongqian; Liu, Haowei; Cao, Yang; Zhang, Guodong (Frontiers in Psychology, 2021)
Nature exposure is known to promote physical and mental health. However, actual nature exposure may be difficult to achieve for the population of people with physical disabilities or chronic conditions. Therefore, many attempts have been made to duplicate nature exposure via media devices, and virtual reality (VR) is deemed as a promising technology due to its advantage in creating a sense of immersion. Generally, current studies suggest that being exposed to virtual nature may contribute to psychological and physiological relaxation. Besides, some pieces of evidence indicate that virtual nature may improve attentional resources, cognitive performance, and pain experience. Although VR is deemed as an advanced media, insufficient evidence was found concerning the advantages of VR over traditional two-dimensional media when it comes to simulated nature exposure. On the other hand, computer-generated (CG) scenarios were found to be more beneficial than 360° videos, and mini-games may be useful in creating an interactive VR format for simulated nature exposure. Further research is needed because of the limited relevant studies.